Screening wild and semi‐free ranging great apes for putative sexually transmitted diseases: Evidence of Trichomonadidae infections. Issue 10 (26th June 2015) - Rushmore, Julie; Allison, Andrew B.; Edwards, Erin E.; Bagal, Ujwal; Altizer, Sonia; Cranfield, Mike R.; Glenn, Travis C.; Liu, Hsi; Mudakikwa, Antoine; Mugisha, Lawrence; Muller, Martin N.; Stumpf, Rebecca M.; et al.
<x xml:space="preserve">Abstract</x> Sexually transmitted diseases (STDs) can persist endemically, are known to cause sterility and infant mortality in humans, and could have similar impacts in wildlife populations. African apes (i.e., chimpanzees, bonobos, and to a lesser extent gorillas) show multi‐male mating behavior that could offer opportunities for STD transmission, yet little is known about the prevalence and impact of STDs in this endangered primate group. We used serology and PCR‐based detection methods to screen biological samples from wild and orphaned eastern chimpanzees and gorillas (N = 172 individuals, including adults, and juveniles) for four classes of pathogens that either commonly cause human STDs or were previously detected in captive apes: trichomonads, Chlamydia spp., Treponema pallidum (syphilis and yaws), and papillomaviruses. Based on results from prior modeling and comparative research, we expected STD prevalence to be highest in females versus males and in sexually mature versus immature individuals. All samples were negative for Chlamydia, Treponema pallidum, and papillomaviruses; however, a high percentage of wild chimpanzee urine and fecal samples showed evidence of trichomonads (protozoa). Analysis revealed that females were more likely than males to have positive urine—but not fecal—samples; however, there was no evidence of age (sexual maturity) differences in infection status. Sequence analysis of chimpanzee trichomonad samples revealed a close relationship to previously described trichomonads within the genus Tetratrichomonas. Phylogenetic comparisons to archived sequences from multiple vertebrate hosts suggests that many of the chimpanzee parasites from our study are likely transmitted via fecal‐oral contact, but the transmission of some Tetratrichomonas sequence‐types remains unknown and could include sexual contact. Our work emphasizes that only a fraction of infectious agents affecting wild apes are presently known to science, and that further work on great ape STDs could offer insights for the management of endangered great apes and for understanding human STD origins. Am. J. Primatol. 77:1075–1085, 2015. © 2015 Wiley Periodicals, Inc.